Integration and Visualization of Maternal and Child Health Data: A Computational Architecture for Analysis and Decision Support - Morsoleto, Ricardo; Batista, Maria C.; Silva, Vinícius A.; Caliari, Juliano de S.; Miranda, Simone Mara F.; Ferreira, Hiran Nonato M. (Companion Proceedings of the Brazilian Symposium on Information Systems (SBSI); 2025: Companion Proceedings of the 21st Brazilian Symposium on Information Systems, 2025)
The increasing volume of data generated by health information systems demands new approaches for analysis and visualization, particularly in the context of public health. This paper proposes the development of a computational architecture to integrate data from three major Brazilian Health Information Systems (HIS): SIM (Sistema de Informação sobre Mortalidade), SINASC (Sistema de Informação sobre Nascidos Vivos), and SIH (Sistema de Informação Hospitalar). The primary objective is to facilitate integrated data analysis and visualization, enabling the extraction of insights to support public policy formulation. Partial results demonstrate the effectiveness of the proposal through the extraction and integration of datasets into a unified database, which allows for temporal, regional, and socio-contextual analyses.